Rice husk ash application in petroleum industry - Samsuri, Ariffin (1999)
The producing performance of a petroleum well depends in great part on a good primary cementing job. In a high-quality cement job, mud and gas channels have been permanently prevented, and there is a complete hydraulic seal between the casing and formation throughout the zone of interest. To properly use the available cements, additives were used to control the major cement properties, including thickening time, fluid-loss rate, free water and compressive strength. Currently, all additives were imported from oversea, therefore studies have been carried out to determine rice husk ash potential to be used as a petroleum well cement additive. The paper presents the results of laboratory experiments on G cement performance with respect to fluid loss, free water, compressive strength and thickening time when rice husk ash (RHA)was added to the cement slurry. Various burning time, RHA particles size and amounts had been used, and Halad 322s as a standard additive. All experiments have been conducted according to American Petroleum Institute (API) Specification 10. The results show that fluid loss volume, free water content and thickening time decreases, and compressive strength increases as the amount of RHA added increases, RHA particles size decreases and burning time increases. RHA performance generally better than Halad 322 in respect to fluid loss and free water, and lower than Halad 322s in term of compressive strength and thickening time, but still within API Spec.10 requirements. Therefore, RHA is suitable for application in petroleum well cementing operation, particularly as fluid loss control agent for class G cement.